Issues of Ethic-identity Crisis in Ngugi’s Matigari and Mda’s The Heart of Redness in the post-colonial era - Athiemoolam, Logamurthie (International Journal of Language and Literary Studies, 2024)
Postcolonial identity takes on various guises in the newly independent African states after the demise of colonialism. In considering these guises, this article examines the various manifestations of post-colonial identity crisis in a comparative study of Matigari by Ngugi wa Thiong’o (1998) and The Heart of Redness by Zakes Mda (2000). The characters in both novels depict two groups in African society during the post-colonial era; namely those who aspire to western values, culture, and beliefs and those who aim to revive their traditional African beliefs and culture. This identity crisis is furthermore exacerbated in terms of those who are aligned to the new nation state, since they feel privileged and connected, and those who feel marginalised and disconnected from the nation state as they are forced to live on the periphery of society. In discussing post-colonial identity crisis in the two novels, common themes such as the influence of western values and culture on African society, conflicts between past, present and future, the petit bourgeoisie, the alienated and the outsider protagonists will be examined comparatively as they are depicted in the novels. The themes shed light on how ethnic-identity crisis is manifested in post-colonial society and how this has an impact on the success of the nation state.